SIMULTANEOUS MAGNETIC FIELD MEASUREMENTS IN SUNSPOTS USING SPECTRAL LINES WITH DIFFERENT LANDE FACTORS - Osipov, S. N.; Lozitsky, V. G. (Одеські астрономічні публікації, 2016)
We present magnetic field measurements in several sunspots observed in June-July 2015 on Horizontal Solar Telescope ATsU-5 of Main Astronomical Observatory of National Academy of Sciences of Ukraine. The Zeeman splittings were measured using I ± V profiles of about ten spectral lines of Mn I, Fe I and Ni I including three lines with negative Lande factors, namely Fe I 5434.527 Å, Fe I 6094.419 Å and Fe I 4995.411 Å ( geff = – 0.014, – 0.218, and – 0.25, respectively). Our main conclusions are the following: a) as rule, spectral lines with largest Lande factors give the strongest measured magnetic fields Bobs in sunspot umbra that can be interpreted as a result of blending the Zeeman π- and σ-components in case of non-longitudinal magnetic field. b) in some places of sunspots, Bobs differs also for lines with close Lande factors, e.g. by Fe I 5432.950 and Ni I 5435.871 (geff = 0.67 and 0.5, respectively). c) lines Fe I 6094.419 Å and Fe I 4995.411 Å with geff < 0 have in sunspots signs of splitting which corresponds to geff > 0. The possible causes of named effects are discussed in short form.